GESTATIONAL ECHO BIOMETRY IN BRACHYCEPHALIC PREGNANT BITCHES - Marcus Antônio Rossi Feliciano; Giovanna Serpa Maciel; Leandro Nassar Coutinho; Vívian Tavares Almeida; Ricardo Ramirez Uscategui; Wilter Ricardo Russiano Vicente (Ciência Animal Brasileira, 2015)
Ultrasonography is an accurate pregnancy diagnostic method, besides being completely innocuous for female and fetuses evaluation. The objective of this paper was to determine the reference values for gestational echo biometry of different breeds of bitches. A total of 25 multiparous females were included in the experiment, five English Bulldog bitches, five Pugs and 15 Shih Tzu, weighing 4-25 kg and aged 4-6 years. The echo biometric assessments were performed during the 2nd, 5th, 6th, 7th and 8th weeks of pregnancy, including gestational vesicle diameter, femur length, placenta thickness, parietal diameter, liver, heart and abdominal diameter and area. Early echo biometric study started at the second week of gestation. Measurements like fetal heart and liver diameter and area are ??still poorly studied, but can provide useful information for early detection of congenital anomalies that may reduce the viability of pregnancy. The significant results (P < 0.001) obtained for biometrics (P < 0.001) of the parietal (r2 = 81%) and abdominal diameter (r2 = 86%), abdominal area (r2 = 80%), femur length (r2 = 84%), cardiac length (r2 = 79%), width (r2 = 79%), area (r2 = 82%) and volume (r2 = 72%) and liver area (r2 = 71%) in brachycephalic conceptus may help to assess the development of fetuses, complementing the conventional gestational ultrasound of bitches and become a model for the study in other breeds of dogs and alternative animal species.